(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
This article covers the theoretical and methodological foundations of the use of simulation technology in teaching English to students in the process of medical education in the form of literature analysis (Literature Review). The need to abandon traditional teaching methods and switch to problem-based learning (PBL) and simulation approaches is analyzed. The study is written in the IMRAD format and is based on scientific works of foreign and domestic scientists. The effectiveness of developing clinical thinking, teamwork, and effective communication skills in a foreign language in students through simulation training is demonstrated.